Tingkah Laku Makan Kambing Lokal Persilangan yang Digembalakan di Lahan Gambut: Studi Kasus di Kalampangan, Palangkaraya, Kalimantan Tengah - R Setianah; S Jayadi; R Herman (Media Peternakan, 2004)
Central Kalimantan is one of the province passed by equator line. The temperature is relatively hot, during the day time is 32 0C and 23 0C during night time. The average rainfall index is 1900-3100 mm per year. This province has remarkably wide peatland area with strong acidity, high organic matter, and low fertility for plant cultivation. Various existing vegetation can be used as feed. Goats are able to utilize many type of grasses, leaves and tree bark. They have high ability to adapt various environments and eat many type of plants. Due to their browsing ability, goats can utilize tall bushes. The objective of this experiment was to study grazing behaviour of Crossed Local goats. The Pattern of grazing behaviour of goats can be used as a basis for managing animals and range land on the peatland areas. The experiment used 5 male goats aged 8-12 months and 5 females aged 10-24 months. Recording methode used One Zero with 15 minutes intervals. Data were analysed using Comparison of Two Samples or t-Test (t student) at level 5%. Result of research indicated that the goat activity in day time (09.00-16.00) was dominated by grazing activity (male 66,28%, female 60,82%). The goats spent more time for eating in the morning and evening (09.00-10.00 and 13.00-16.00). Grazing rumination and resting activities during investigation between male and female were not significantly different. Browsing is the most activity observed compared to other activities. Crop types are diverse in peatland areas. The result show that sasendok vegetation (Plantago mayor), Delingu (Dianella ensifolia sp.) and Kelakai (Stenochlaena palustris) were the most preferred vegetation by the goats on the peatland areas. Key words: grazing behaviour, Crossed Local goats, peatland